Designing, Implementing, and Managing a National Emergency Medical Service in Sierra Leone. Issue 1 (1st February 2021) - Ragazzoni, Luca; Caviglia, Marta; Rosi, Paolo; Buson, Riccardo; Pini, Sara; Merlo, Federico; Della Corte, Francesco; Vandy, Matthew Jusu; Jambai, Amara; Putoto, Giovanni
Abstract: Sierra Leone is one of the least developed low-income countries (LICs), slowly recovering from the effects of a devastating civil war and an Ebola outbreak. The health care system is characterized by chronic shortage of skilled human resources, equipment, and essential medicines. The referral system is weak and vulnerable, with 75% of the country having insufficient access to essential health care. Consequently, Sierra Leone has the highest maternal and child mortality rates in the world. This manuscript describes the implementation of a National Emergency Medical Service (NEMS), a project aiming to create the first prehospital emergency medical system in the country. In 2017, a joint venture of Doctors with Africa (CUAMM), Veneto Region, and Research Center in Emergency and Disaster Medicine (CRIMEDIM) was developed to support the Ministry of Health and Sanitation (MOHS) in designing and managing the NEMS system, one of the very few structured, fully equipped, and free-of-charge prehospital service in the African continent. The NEMS design was the result of an in-depth research phase that included a preliminary assessment, literature review, and consultations with key stakeholders and managers of similar systems in other African countries. From May 27, 2019, after a timeframe of six months in which all the districts have been progressively trained and made operational, the NEMS became operative at national level. By the end of March 2020, the NEMS operation center (OC) and the 81 ambulances dispatched on the ground handled a total number of 36, 814 emergency calls, 35, 493 missions, and 31, 036 referrals.